As Births Diminish and Deaths Increase, Natural Decrease becomes More Widespread in Rural America*. (28th November 2020) - Johnson, Kenneth M.
Abstract: Even before the onset of the Covid‐19 pandemic, the U.S. population growth rate last year was the lowest in 100 years. And, from 2010 to 2019 nonmetropolitan America lost population for the first time in history. Diminished natural increase was a major contributor to this and also accelerated the incidence of natural decrease (more deaths than births), particularly in rural America. Deaths exceeded births in 46 percent of all U.S. counties—a near record high. Nearly 79 percent of these natural decrease counties were nonmetropolitan. This research uses recent data and a multivariate spatial regression model to update our understanding of the growing incidence of natural decrease in both rural and urban America. In light of the mortality increase and likely fertility declines stemming from the Covid‐19 pandemic, these findings have significant implications for future nonmetropolitan demographic trends.